Importance of health spending in the Base of the Pyramid (BoP) population in Táchira, Venezuela (2022)
Introduction. This research analyzes whether health is among the three main expenditures that a household allocates from its income in the population at the base of the pyramid (BoP) and whether there is an association with people belonging to different socioeconomic levels of the BoP in the state of Táchira, Venezuela. Methods. Data was obtained from a structured questionnaire applied to a sample of 1,398 households in the Táchira region, Venezuela, which were classified by socioeconomic levels through the construction of a global synthetic index that, through scales, allows segmenting households by poverty conditions, from the most intense poverty condition to the most favorable non-poverty condition respectively, resulting in 675 households at the base of the pyramid. Results. For households at BoP levels 2 and 3, health expenditures are presented in greater proportion than in level 1, with a value of 55.74% and 51.77%, respectively, while in level 1 only 26.67% of households included health ex- penditures among the top three, likewise there is evidence of association between the BoP level and the categories of expenditures on housing, public services, health, and education. Conclusions. The results of this research also confirm the theory that the BoP population is heterogeneous due to socio-cultural differences, evidenced in the association that exists between health expenditure and socioeconomic level, when rejecting the hypothesis of independence, which means that the proportion of households that consider health expenditure important varies depending on which level of the BoP they are in. Keywords: base of the pyramid, socioeconomic level, health spending, poverty